Justice and Peace in a Renewed Caribbean - Perkins, Anna Kasafi. author. aut Link
XX, 307 p.
Keywords: This collection of critical essays and personal reflections explores the insights provided by official statements of the Roman Catholic Bishops of the Caribbean. In so doing, it presents a critical reading of the corpus with a view to presenting its relevance to the regional and global conversation on matters of human flourishing.